OBESITY AND ENDOMETRIAL HYPERPLASIA AND CANCER IN PREMENOPAUSAL WOMEN: A SYSTEMATIC REVIEW - Hilman, Feisal; Subhakti, M Alvian; Prabowo, Rafik (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Endometrial cancer (EC) represents the most common malignancy of the female reproductive tract. The precursor lesion for endometrioid adenocarcinoma of the endometrium, which comprises the majority of ECs, is endometrial hyperplasia (EH). EH is a noninvasive, abnormal proliferation of the endometrial lining of the uterus and associated with a significant risk of concurrent EC or progression to EC. The leading symptoms of EH are bleeding disorders in premenopausal women and vaginal bleeding in postmenopausal women. The most important risk factor is chronic exposure to unopposed estrogen. The aim: This study aims to show obesity and endometrial hyperplasia and cancer in premenopausal women. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 81 articles, whereas the results of our search on SagePub brought up 112 articles. The results of the search conducted for the last year of 2013 yielded a total 29 articles for PubMed and 78 articles for SagePub. The result from title screening, a total 5 articles for PubMed and 13 articles for SagePub. In the end, we compiled a total of 8 papers. We included five research that met the criteria. Conclusion: The nomogram of EH/EC is significantly associated with risk factors, namely BMI, PCOS, anemia, infertility, menostaxis, AUB type, and endometrial thickness. The nomogram model can be used to predict the EH/EC risk and rapidly screen risk factors in a women population with high risk.